Temporal monitoring of Ghamu bar glacial lakes using remote sensing and GIS - Hussain, Alamgeer; Bano, Dilshad (International Journal of Advanced Geosciences, 2019)
The trends of glacial lakes formation and glacial lake outburst flooding events have been increased across Himalayan Karakorum Hindu Kush (HKH) ranges during last decade due to increase in global warming. This research is addressing the temporal monitoring of ghamu bar glacial lakes using remote sensing and GIS. Landsat images of 1990, 2000, 2010 and 2015 were used to map temporal glacial lakes using normalized difference water index (NDWI) index. The results of normalized difference water index were validated through modified normalized difference water index and field photographs. Temporal variability shows that, glacier lake area has been increase from 1990 to 2015. In 1990 total area of lake was 0.052 sq, which further increased 0.0423 in 1995 than it decreases to 0.314 in 2000 due to detached of debris cover moraine from glacier tongue and it reach 0.0846 sq.km in 2005. The area gradually increased up to 0.1296 sq.km in 2010 and it goes up to 0.157 sq.km 2015. The overall increase in area are expanding at an accelerated rate in past two decades, indicating that Darkut glacier is more vulnerable toward climate change through increase in size and volume ofghamu bar glacial lakes. There is need for vigilance in monitoring of ghamu bar glacial lake through high resolution remote sensing data and development of Geo-database enabling more details about past and future lakes behaviors toward climate change impacts.Â Â Â Â